Importancia ecológico-económica del aprovechamiento de los bosques - Dávalos Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
Satisfying the needs of the population in a rational, permanent and ecologically sensible way is the greatest challenge facing modern societies. Forest resources have played a significant role in the development of civilization and have contributed significantly to national income. This is not the case in Mexico. The central hypothesis of this paper is that the use of wood is not harmful to the environment. Wood is one of the most benign construction materials available. It is a natural, renewable resource that is economically attractive for structural and architectural uses. Non-renewable materials use up a great deal more energy per production unit than wood. Wood as a construction material has many advantages. As an insulating material, it is more energetically efficient. Its structural efficiency, in terms of the energy required to produce it, is greater. Growing forests are huge carbon sinks and no other material performs the ecological service of reducing the greenhouse effect. Another notable benefit is the role of the forest as an element of the biosphere that regulates hydrology and earth biogeochemistry. The secret to reaping all of these benefits is to cultivate forests, to use them for the production of commodities with low energy expenditure and to let them grow so that they produce more oxygen, capture carbon dioxide and maintain forest soils intact.